Mr asked in Science & MathematicsMathematics · 1 month ago

How to simplify these expressions?

V^(-1/3) / V^(-2/3) V^5

(4v^2)^(5/2) / (u^6)^3/2

(Cubert x^-2) / x^(4)sqrt(x)

X^(-9/3) / x^(2/3) sqrt x^6

2 Answers

Relevance
  • 1 month ago
    Favorite Answer

    v^(-1/3) / v^(-2/3) v^5

    = v^16/3

  • ted s
    Lv 7
    1 month ago

    use the property of exponents...see 'wikipedia.org' , type in 'exponents ' and READ.....examples:

    ³√ (x^-2) ≡ x^(-2/3) ≡ 1 / x^(2/3)...

    V^(-2/3) V^5 ≡ V^(-2/3 + 5) = V^(13/3)

Still have questions? Get your answers by asking now.